Immune thrombocytopenia in infants: a retrospective study with comparison to toddlers - Anselm Chi-wai Lee (Singapore Medical Journal)
Introduction: Immune thrombocytopenia (ITP) is the most common cause of acquired bleeding in childhood, but little is known about the clinical course and outcomes in infants with ITP. Methods: This is a retrospective study of all infants (1–12 months of age) and toddlers (13–47 months of age) diagnosed with ITP from a single centre during a 13-year period. The following data were compared between the two patients groups: demographics, severity of bleeding, platelet counts, duration of illness, development of chronic ITP, treatment and association with recent vaccination. Results: Twenty-two infants and 30 toddlers were diagnosed and followed up for ITP during the study period. Infants with ITP generally had minor or mild bleeding (19, 86.4%) and seldom required treatment (7, 31.8%), and their thrombocytopenia resolved at a mean of 1.90 months after diagnosis. Besides age, the sex ratio, severity of bleeding, platelet counts and proportion that required treatment were comparable between infants and toddlers. Fewer infants developed chronic ITP (1/22 vs. 9/30, P = 0.032), but more infants had a history of vaccination in the preceding 6 weeks prior to diagnosis of ITP (13/22 vs. 1/30, P < 0.001). Conclusion: ITP in infants is almost always a self-limiting and transient illness, and the majority of cases do not require treatment.